The Development of an Inquiry-Based Laboratory Manual for Student of Biology Education - Putri, Azza Nuzullah (LPPM Undiksha, 2021)
Inquiry enables the student to learn through many activities that can improve student attitudes, processes, and thinking skills. Inquiry learning helps students develop their ability to solve the problem, think critically and reflectively. Applying inquiry-based activities in laboratory courses is one way to prompt the student-centered learning in general biology courses. The research aimed to develop a valid and practical inquiry-based laboratory manual for biology education students. This study used the ADDIE model to develop the product, the stages involve analysis, design, development, implementation, and evaluation. The implementation was conducted on 30 biology education students who take general biology courses. The data were collected by the validation sheet and questionnaire of student responses. The inquiry-based laboratory manual that has been developed gets a very decent category as a validation result. Practical of inquiry-based laboratory manual obtained from student response and it got a very practical category. The product is expected able to guide the student to do an inquiry process in laboratory activities.